Foreign tourists’ assessment of translation errors in Vietnamese - English translations of culture-specific terms in object labels at Vietnam Museum of Ethnology = Đánh giá của du khách nước ngoài về các lỗi dịch trong bản dịch Việt-Anh của các thuật ngữ mang đặc trưng văn hóa trên tên hiện vật tại Bảo tàng Đân tộc học Việt Nam - Nguyễn, Thị Thùy Trang (2021)
Readers are the ultimate users to decide the success of a text translation, yet this fact is often neglected in research about Vietnamese – English tourism text translations. Additionally, cultural translation has long proved itself to be of great importance since Vietnam opened the door to a flat world. This study thus aimed at shedding light on the reactions of foreign tourists to translation errors of object labels at the Vietnam Museum of Ethnology and their expectations to improve the translation quality of this text type. The researcher based on a study by Bui (2014) about procedures and errors in object label translations at VME to select research subjects (21 translation errors of four types) according to ATA framework. The use of questionnaire in qualitative interview (questerview) was applied as the method of collecting data from 20 random English native speakers visiting VME. Then, both statistical analysis (for questionnaires) and content analysis (for interviews) were employed to answer the research questions. The researcher figured out several interesting findings. First, each translation error type exerted its different impacts at un-identical levels of seriousness on foreign tourists, thus receiving different evaluations from them. Also, three main factors that might impact readers’ translation quality assessment were (1) tourists’ background knowledge about the source language’s culture, (2) their personal interest in the objects and (3) their familiarity with the terms. More interestingly, it was pointed out that informativeness ranked first in terms of importance when it came to foreign tourists’ expectations for a translation of cultural terms in object labels. Hence, the participants suggested using descriptive equivalent translation procedure and asking for comments and recommendations from foreigners or experts to improve the translation quality of object labels at the museum